The effect of tax ratio and good government governance on economic growth - Singagerda Faurani Santi, Marselina, (Opción, 2019)
The purpose of this study is to investigate the effect of tax ratio and good government governance on economic growth via comparative quantitative research methods. As a result, all elements of government such as government effectiveness, regulatory quality, rule of law, control of corruption and taxes ratio effect on economic growth. In conclusion, to promote economic growth, in addition to reforming the taxation sector, the government must implement good government governance by providing the best service to the community, eradicating corruption, enforcing rules and regulations, creating rules and legislation of good quality, fair and consistently run.